Current and Potential Therapeutic Strategies for Hemodynamic Cardiorenal Syndrome - Obi, Yoshitsugu (Cardiorenal Med, 2016)
BACKGROUND: Cardiorenal syndrome (CRS) encompasses conditions in which cardiac and renal disorders co-exist and are pathophysiologically related. The newest classification of CRS into seven etiologically and clinically distinct types for direct patient management purposes includes hemodynamic, uremic, vascular, neurohumoral, anemia- and/or iron metabolism-related, mineral metabolism-related and protein-energy wasting-related CRS. This classification also emphasizes the pathophysiologic pathways. The leading CRS category remains hemodynamic CRS, which is the most commonly encountered type in patient care settings and in which acute or chronic heart failure leads to renal impairment. SUMMARY: This review focuses on selected therapeutic strategies for the clinical management of hemodynamic CRS. This is often characterized by an exceptionally high ratio of serum urea to creatinine concentrations. Loop diuretics, positive inotropic agents including dopamine and dobutamine, vasopressin antagonists including vasopressin receptor antagonists such as tolvaptan, nesiritide and angiotensin-neprilysin inhibitors are among the pharmacologic agents used. Additional therapies include ultrafiltration (UF) via hemofiltration or dialysis. The beneficial versus unfavorable effects of these therapies on cardiac decongestion versus renal blood flow may act in opposite directions. Some of the most interesting options for the outpatient setting that deserve revisiting include portable continuous dobutamine infusion, peritoneal dialysis and outpatient UF via hemodialysis or hemofiltration. KEY MESSAGES: The new clinically oriented CRS classification system is helpful in identifying therapeutic targets and offers a systematic approach to an optimal management algorithm with better understanding of etiologies. Most interventions including UF have not shown a favorable impact on outcomes. Outpatient portable dobutamine infusion is underutilized and not well studied. Revisiting traditional and novel strategies for outpatient management of CRS warrants clinical trials.